Pengembangan game edukasi naga tangga berbasis problem based learning untuk meningkatkan berpikir kritis siswa SD - Rizky Putra Solihin; Agus Hasby Noor; Faridillah Fahmi Nurfurqon (COLLASE (Creative of Learning Students Elementary Education), 2026)
This research was initiated by the low critical thinking skills of students in Pancasila Education. This actual condition was reflected in the initial test (pre-test) results of fourth-grade students at SDN Cipatat, which only reached an average score of 52.81. The primary objective of this study is to design and validate the efficacy of the Naga Tangga digital game integrated with the Problem-Based Learning (PBL) model to optimize students' critical thinking skills. The approach applied in this study was the Research and Development (R&D) method based on the ADDIE model procedure. During the product efficacy testing phase, a pre-experimental design was implemented. The selected model was the One-Group Pretest-Posttest Design, involving 32 fourth-grade students as research subjects. Data were collected through expert validation instruments, student response questionnaires, and critical thinking skills tests in the form of essays. The accuracy of the quantitative data was ensured through a series of prerequisite tests. Data computation was performed using paired t-tests via statistical software, followed by N-Gain score calculations to determine the level of product effectiveness. The results indicated that the Naga Tangga Digital educational game is highly feasible, achieving an expert validation percentage of 87.5% and meeting excellent practicality criteria with an average student response score of 3.84. Furthermore, the implementation of the product proved effective in significantly improving students' critical thinking skills, as demonstrated by the average post-test score of 85.69 and an average N-Gain score of 0.70, which falls into the high category. This study concludes that the systematic integration of PBL syntax into digital game mechanics effectively elevates students' critical thinking skills in solving contextual problems in elementary schools.